Impact of different magnification levels on visual caries detection with ICDAS. Issue 12 (December 2015) - Neuhaus, KW; Jost, F; Perrin, P.; Lussi, A
Abstract: Objectives: The aim of this in vitro study was to examine the effect of different levels of magnification on the accuracy and reliability of visual caries detection using ICDAS criteria. Methods: Occlusal surfaces of 100 extracted molars were assessed by 14 examiners (3rd and the 4th year dental students and dentists) using no magnification aids, a 2.5× Galilean loupe, a 4.5× Keplerian loupe, or a surgical microscope with 10× magnification. The assessments were repeated on a different day. Sensitivity, specificity, AUC and reliabilities were calculated according to the gold standard of histology. Results: We found that with increasing magnification, the number of surfaces rated as "sound" (ICDAS code 0) decreased, while the number of surfaces with a localized enamel breakdown (ICDAS code 3) increased. While the sensitivities increased, the values of the specificities decreased to an unacceptably low level irrespective of the clinical experience of the examiners. Conclusions: ICDAS seems to be optimized for natural vision up to 2.0× magnification and not for high magnifications. The use of powerful magnification in visual caries detection involves the risk of unnecessary and premature invasive treatment. Clinical significance: This paper discusses when it does and does not make sense to use magnification devices for visual caries detection using ICDAS criteria. Strong magnifications should be refrained from for this purpose.